If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(y + 7) + -8(3y + -7) = -19y + 2 Reorder the terms: 5(7 + y) + -8(3y + -7) = -19y + 2 (7 * 5 + y * 5) + -8(3y + -7) = -19y + 2 (35 + 5y) + -8(3y + -7) = -19y + 2 Reorder the terms: 35 + 5y + -8(-7 + 3y) = -19y + 2 35 + 5y + (-7 * -8 + 3y * -8) = -19y + 2 35 + 5y + (56 + -24y) = -19y + 2 Reorder the terms: 35 + 56 + 5y + -24y = -19y + 2 Combine like terms: 35 + 56 = 91 91 + 5y + -24y = -19y + 2 Combine like terms: 5y + -24y = -19y 91 + -19y = -19y + 2 Reorder the terms: 91 + -19y = 2 + -19y Add '19y' to each side of the equation. 91 + -19y + 19y = 2 + -19y + 19y Combine like terms: -19y + 19y = 0 91 + 0 = 2 + -19y + 19y 91 = 2 + -19y + 19y Combine like terms: -19y + 19y = 0 91 = 2 + 0 91 = 2 Solving 91 = 2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 4x-19x=105 | | 12s^2+13s-35=0 | | 5.5a+2=10.5 | | -6+5b=6b | | -5v+25=2(v+2) | | 2x^2-7x+5= | | -(d+12)-3=8 | | 36x^2+28x=0 | | 9u=v | | 2-8m-5=11 | | -237=-3(15+4a) | | F(-4a)= | | 3(x+2)6(-3-x)=4(2x-1) | | 16+2y=9 | | 43-3x+3= | | -8x+12=20 | | -3(2x+7)=-75 | | 3x+6-18-6x=8x-4 | | 3y^2-2y-1= | | -8+12=20 | | 3x-43+3= | | y-7+10-4x+6x+2y= | | (8k-1)(4k-3)=0 | | 126=2x+2(2x-6) | | 5x+7=75 | | (4c+2g)(4c-2g)=0 | | 2x^2-8x+8=0 | | 8x+6-3x-8+2y-6y= | | 7(k-6)+8=-13 | | 0.2(500-2.3x)=3.8(3x-3000) | | 2k^2-18= | | -252=-7(x+19) |